Pengembangan Media Virtual Reality Pada Muatan Pelajaran IPA Kelas VI Sekolah Dasar - Mardiki Supriadi; L. Virginayoga Hignasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2019)
The media is based on Virtual Reality, which can help educators as a learning medium to explain the material content of science lessons in learning activities. The purpose of this study is to produce a virtual reality-based learning media on the content of elementary school science classes IV. This research is a development study with a 4D development model from Thiagarajan that has been modified. This development model consists of the stages define (definition), design (design), develop (development). The research and development stage is carried out until the develop stage. The results showed that the virtual reality media is very feasible to be used in grade VI elementary school on the subject of natural science by referring to the results of the validation of the experts. The results of validation by media experts are 85% or Very Valid. Material expert validation on the media consisted of 5 aspects. The results of validation by material experts are 82% or Very Valid. The validation of the field application experts to the developed media consisted of 3 aspects. The results of validation by the field application experts are 89% or Very Valid.